Assessment of the association between plant-based dietary exposures and cardiovascular disease risk profile in sub-Saharan Africa: a systematic review - Tatum Lopes; Annalise E. Zemlin; Rajiv T. Erasmus; Samukelisiwe S. Madlala; Mieke Faber; Andre P. Kengne (BMC, 2022)
Abstract Background Studies have investigated dietary attributes associated with cardiovascular disease (CVD) risk in Africa. However, there has been no effort to critically assess the existing evidence. This systematic review examined available evidence on the association between plant-based dietary exposures and CVD risk profile in Africa. PROSPERO registration number: CRD42020159862. Methods We conducted a literature search for observational studies reporting on plant-based dietary exposures in relation to CVD risk profile in African populations. PubMed-Medline, Scopus, EBSCOhost, and African Journals Online platforms were searched up to 19 March 2021. Titles and abstracts of the identified records were screened independently by two investigators. The quality of the studies was also assessed independently. Results Of 458 entries identified, 15 studies published between 2002 and 2020 were included in this review. These studies originated from 12 sub-Saharan Africa (SSA) countries. Sample sizes ranged from 110 to 2362, age from 18 to 80 years; and majority of participants were females (66.0%). In all, four plant-based dietary exposures were identified across SSA. Sixty percent of the studies reported a significant association between a plant-based dietary exposure with at least one CVD risk factor such as hypertension, diabetes mellitus, dyslipidaemia, overweight/obesity, and metabolic syndrome. Conclusions The few available studies suggest that there may be a protective effect of plant-based dietary exposures on CVD risk profile in the African setting. Nonetheless, more elaborated studies are still needed to address plant-based diet (PBD) adherence in relation with CVD risk in African populations.